2018
DOI: 10.25135/rnp.33.17.09.145
|View full text |Cite
|
Sign up to set email alerts
|

Phillipsins A and B from Zingiber phillippsii Mood & Theilade in Borneo

Abstract: Abstract:Two new aromatic compounds, phillipsins A (1) and B (2) were isolated from the Bornean wild ginger Zingiber phillippsii Mood & Theilade, and were characterized based on spectroscopic data (HRESI-MS, FTIR as well as 1D and 2D NMR). These metabolites also exhibited strong antifungal activity against selected fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Ginger (Zingiber officinale Roscoe), a popular spice with aromatic and pungent components, is also utilized in traditional medicine for its healing properties of various gastrointestinal diseases, metabolic diseases, rheumatism, arthritis, pain, and muscle discomfort [1][2][3]. Moreover, numerous studies have reported that ginger exhibits antibacterial, antifungal, and anticancer properties [4][5][6]. Ginger rhizome is widely cultivated as an important economic crop.…”
Section: Introductionmentioning
confidence: 99%
“…Ginger (Zingiber officinale Roscoe), a popular spice with aromatic and pungent components, is also utilized in traditional medicine for its healing properties of various gastrointestinal diseases, metabolic diseases, rheumatism, arthritis, pain, and muscle discomfort [1][2][3]. Moreover, numerous studies have reported that ginger exhibits antibacterial, antifungal, and anticancer properties [4][5][6]. Ginger rhizome is widely cultivated as an important economic crop.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of the fungistatic on hyphae was performed by incorporating the pure compound solutions (12.5, 25.0, 50.0, 100.0 μg/mL) onto PYGS agar in a petri dish followed by inoculation of six tested fungal strains [21][22][23]. The MIC was determined visually as the lowest concentration showing no hyphal growth after they were incubated at 25 °C for 7 days.…”
Section: Antifungal Assaymentioning
confidence: 99%
“…The procedure was modified from known method [15,16]. The MIC was determined visually as the lowest concentration showing no hyphal growth when they were incubated at 25 °C for 7 days.…”
Section: Antifungal Bioassaymentioning
confidence: 99%